A formação da identidade virtual na comunidade do Orkut - Vaz, Raphael do Amaral (2011)
This research aims to study the construction of identity in the virtual community Orkut, identifying the reasons for the choice of identity and how individuals construct their virtual identity, aims to also determine what features and qualities are virtual identity, identify similarities and differences between virtual and real life identity, and, finally, to observe how the subject relates to your friends Orkut and how it relates to them in real life. For this, we conducted semistructured interviews with ten patrons of that community (men and women) between 20 and 32 years. The respondents' answers were categorized from some common words found in them. The results were analyzed using the theoretical framework of Analytical Psychology. It was observed that results in the formation of virtual identity is based on the various ways in which users work in this social network. Established through interaction between friends, many users design their wishes on Orkut to be seen by others as they would like to see. Raised through the categories of responses, we can observe that the construction of virtual identity that occurs from projective action of the subject in relation to the other members of social networking and also always having a relationship with the real identity of the subject. We can say that the formation of virtual identity in this study had a fundamental importance to clinical psychology, as we understand the permanence of Orkut users in a psychic link is established between the subject and digital social network, providing projective actions of psychic contents Persona